Consolidating the Covid Debt - Christian Keuschnigg; Julian Johs; Jacob Stevens (Center for Economic Studies and ifo Institute (CESifo), 2021)
One of the main functions of public debt is to smooth taxes and spending over time. In the Covid crisis, the Maastricht deficit restrictions were temporarily suspended to allow for large temporary deficits. As recovery sets in, countries are confronted with the task of consolidating the Covid debt. This paper explores a fiscal consolidation strategy combined with growth enhancing tax and expenditure reform. We quantitatively illustrate that this reform based strategy, by reaping substantial efficiency gains and inducing strong growth, eliminates the Covid debt, protects per capita social entitlements and yet avoids increasing tax rates. With slow consolidation, marginal tax rates are reduced right from the beginning.
Keywords: E62; H24; H25; H55; H63; 330; Covid debt; fiscal consolidation; tax and expenditure reform; growth